Determinação simultânea de aspirina e ácido ascórbico em medicamentos usando análise por injeção em fluxo com detecção amperométrica - Miranda, Joyce Aparecida Tavares de (2011)
The present study investigated a simple, low-cost and, high analytical frequency method for simultaneous determination of ascorbic acid (AA) and acetylsalicylic acid (ASA) in pharmaceutical formulations. The methodology is based on flow injection analysis with multiple-pulse amperometric detection (FIA-MPA) using boron-doped diamond (BDD) as working electrode. The oxidation current peak of AA reaches a maximum near to 0.9 V and for salicylic acid (hydrolyzed AAS) near to 1.35 V (acetic acid/acetate buffer; pH = 4,7). The strategy used for simultaneous determination of the two compounds by FIA-MPA was the following: (1) +0.90 V/50 ms: AA oxidation and its selective quantification; (2) +1.35 V/50 ms: Oxidation of both AA and AS compounds. AS can be then quantified by subtraction of the currents obtained from both potential pulses (using a correction factor), because the oxidation currents of AA are not the same at both potential pulses. The current from the oxidation of AS is obtained from the following equations: factor = IAA +1.35 V/IAA +0.9 V IAS = I1.35 V (I0.90 V x factor) (3) +0.00 V/300 ms: applied to avoid contamination of the working electrode surface. The proposed method presented linear range response between 10 and 90 μmol L-1 and between 16 and 200 μmol L-1 for AA and AS, respectively. The repeatability study (n = 10) demonstrated that the method is stable with the RSD equal to 0.5 %. The analytical frequency was estimated to be 125 injections per hour and the limit of detection of 174 and 164 nmol L-1 for AA and AAS, respectively. Results were compared to those obtained by an HPLC method and statistical analysis was used to compare these results. At a 95% confidence level it was verified that both methods showed similar results (Student s t-test) and equivalent accuracies (F test). Additional studies for simultaneous determination of AA and AAS were also carried out using Batch Injection Analysis (BIA) and Square Wave Voltammetry (SWV).